Implementasi Manajemen Kearsipan Berbasis Lotus Notes - Setiawan, Alexander; Santoso, Leo Willyanto (Sainstek, 2008)
This research, compiled an alternative of trouble-shooting in the form of archiving management implementation by using technology Lotus Domino Server version of 8.0.5 and Lotus Notes version of 8.0.5. This archiving management information system is very wide and complex on that account in this research to study problem of observation (auditing) done by Internal Control Identity. This study concerning Information systems to based on the literature. Data collecting based on data any kind of which required to design this information systems. After gathering data, the design an information system and to testing the design. Key Words: management, file system, lotus notes.